Health related quality of life in elderly of nursing homes, medellin-colombia, 2012 (2014)
Introduction: Elderly in Medellin present conditions of economic, social, environmental and general health vulnerability; in nursing homes shows further deterioration of health related quality of life (HRQOL). Objective: To compare the profile of HRQOL of adults over public and private nursing homes in Medellin. Materials and methods: Across-sectional correlational study in 220 elderly selected using probability sampling. WHOQOL-BREF was used and the clinical data of each individual. We assessed scale reliability using Cronbach's alpha, internal consistency and discriminant validity using Pearson correlations, analyzes of HRQOL were based on summaries measures and frequencies, non-parametric and parametric tests and lineal regression. Results: We found 50 % hypertension, 23.6 % diabetes mellitus, dislipidemia 22.3 % and 15 % osteoporosis. The WHOQOL-BREF showed excellent reliability, internal consistency and discriminant validity, the best score was the psychological health and worst in social relationships. We found no differences in HRQOL by type of nursing home. The main factors related to HRQL were satisfaction with family support and participation in social groups. Conclusion: We identified some determinants of HRQOL, this demonstrated its multidimensionality; relevant information for further research and for the implementation of public health policies and clinical actions.